A Review Of Tolerance Education In The Development Of Children To Adulthood - Bambang Afriadi (STAI Miftahul Ula Nganjuk, 2020)
The purpose of this study is to reveal the objective facts of children to recognize differences in their developmental period to the next stage of development in society. The method of writing this article is to use primary and secondary data related to this topic. Supporting data from the author is from the results of the 2017 national religious harmony questionnaire, in the Jakarta area of Johar Baru District, Johar Baru and Kemayoran District, Kemayoran District, as primary data from this study. In this discussion the fundamental is the collection of discussion reports that are relevant to the issues discussed as secondary data, secondary data sources in the form of journal articles, news articles, books and other supporting data. The results of the discussion showed tolerance, who wanted to understand other points of view. It also means learning a different reality. Teachers and parents and even the community must be aware of the ways in which the reasons for a five-year-old child differ from the reasons for a fifteen-year-old child, it is also important to realize that school structure and expectations influence the way children grow and learn. Whereas the data questionnaire shows that the tolerance level between the two districts is in a relatively good position. The answers to the results of this study indicate that children are also accustomed to living and playing or socializing with diversity from an early age.